Sustainable adaptation of commercial inland fishing?-Lessons learnt from subarctic Lake Inari, Finland - Turunen, Minna T.; Rasmus, Sirpa; Montonen, Marja; Salonen, Erno; Lehtonen, Ilari (Springer Science and Business Media Deutschland GmbH, 2025)
We studied commercial fishers' observations and experience-based knowledge in combination with long-term monitoring data in order to gain a holistic view of the adaptation of fishers to climate change and other drivers on Lake Inari. Fishers' main sustainability concerns included degradation of the environment, overfishing, and lack of decision-making power. The fishery and fishing have changed due to increased water temperature and lake productivity; the open-water period has become longer and winter fishing season shorter and spring-spawning species, such as pike and perch, have become more common. Fishers' responses to reduce risks and cope with future uncertainty included both long- and short-term adaptation-achieved through diversification, flexibility, innovation, and mobility. The responses of fishers to multiple changes are variable and based on individual rather than community behavior. We argue that diverse fishing strategies support the adaptation capacity and sustainability of commercial fishing. Sustainable adaptation of commercial inland fisheries could be further enhanced by better monitoring of the hydrology and fishery, by supporting social relations and communication, and through decision-making based on both scientific and fishers' knowledge. Peer reviewed